2008
DOI: 10.1095/biolreprod.107.065359
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-Beta-Cyclodextrin Improves Fertilizing Ability of C57BL/6 Mouse Sperm after Freezing and Thawing by Facilitating Cholesterol Efflux from the Cells1

Abstract: Sperm cryopreservation provides an economical means of storing genetically engineered mouse strains in resource facilities. In general, relatively high fertilization rates are obtained for frozen/thawed sperm of the CBA/JN, DBA/2N, and C3H inbred strains and some F1 hybrid strains. However, the fertilization rate for frozen/thawed sperm of C57BL/6, which is the main strain of genetically engineered mice, remains very low. Therefore, it is necessary to establish an in vitro fertilization (IVF) method for cryopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(172 citation statements)
references
References 39 publications
7
165
0
Order By: Relevance
“…Type A, intact acrosome; type B, condensed acrosome; type C, collapsed acrosome; and type D, elimination of the acrosome MβCD-treated spermatozoa and ICSI zygotes derived from MβCD-treated spermatozoa. These findings demonstrate that MβCD has no detrimental effect on sperm chromatin, and cytogenetically supports the previous finding that IVF embryos derived from MβCD-treated spermatozoa show normal developmental ability [15]. In contrast, the increased incidence of structural chromosome aberrations was found in ICSI zygotes derived from acrosome-intact spermatozoa after incubation in H-TYH without MβCD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Type A, intact acrosome; type B, condensed acrosome; type C, collapsed acrosome; and type D, elimination of the acrosome MβCD-treated spermatozoa and ICSI zygotes derived from MβCD-treated spermatozoa. These findings demonstrate that MβCD has no detrimental effect on sperm chromatin, and cytogenetically supports the previous finding that IVF embryos derived from MβCD-treated spermatozoa show normal developmental ability [15]. In contrast, the increased incidence of structural chromosome aberrations was found in ICSI zygotes derived from acrosome-intact spermatozoa after incubation in H-TYH without MβCD.…”
Section: Discussionsupporting
confidence: 90%
“…It has been demonstrated that methyl-β-cyclodextrin (MβCD) allows mouse spermatozoa to capacitate by promotion of cholesterol efflux from the plasma membrane [13][14][15]. Calcium ionophore A23187 is commonly used to induce the acrosome reaction in mammalian spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a possibility that a medium containing no Ca 2+ has some other effect on the fertility of the frozen sperm. Takeo et al [23] reported that MBCD improves the fertility of frozen C57BL/6 sperm by stimulating cholesterol efflux. It will be important to investigate whether or not SP in a medium containing no Ca 2+ stimulates cholesterol efflux from the cell, and whether or not MBCD affects acrosome loss.…”
Section: Discussionmentioning
confidence: 99%
“…When partial zona pellucida nicking [18,19] or intracytoplasmic sperm injection (ICSI) [20,21] is performed to increase fertility, post-thawed C57BL/6J sperm can fertilize a high percentage of eggs. Improved IVF rates with intact oocytes have rarely been reported using motile sperm separated from thawed suspension [16,22] or methyl-beta-cyclodextrin (MBCD) stimulating cholesterol efflux from thawed sperm [23]. Successful IVF with fresh sperm depends on the media used.…”
mentioning
confidence: 99%
“…Mechanical damage to the sperm membrane occurs most often in spermatozoa from the C57BL/6 (B6) strain, one of the standard inbred stains of genetically engineered mice. This has prompted several technical improvements for cryopreservation of B6 spermatozoa by modifying the composition of the cryopreservation solution or the sperm preincubation medium [16][17][18][19].Little attention has been given to the containers used for freezing spermatozoa because the plastic straws currently used are generally satisfactory. However, these straws are used specifically for sperm freezing and are less familiar than conventional cryotubes in most laboratories.…”
mentioning
confidence: 99%